(125)I brachytherapy of locally advanced non-small-cell lung cancer after one cycle of first-line chemotherapy: a comparison with best supportive care - Song, Jingjing (Onco Targets Ther, 2017)
OBJECTIVES: The objective of this study was to assess the efficacy of computed tomography (CT)-guided (125)I brachytherapy alone in improving the survival and quality of life of patients with unresectable locally advanced non-small-cell lung cancer (NSCLC) after one cycle of first-line chemotherapy. PATIENTS AND METHODS: Sixteen patients with locally advanced NSCLC were treated with CT-guided (125)I brachytherapy after one cycle of first-line chemotherapy (group A). Sixteen patients who received only best supportive care (group B) were matched up with the patients in group A. Primary end point included survival, and secondary end point included assessment of safety, effectiveness of CT-guided (125)I brachytherapy, and improvement in the quality of life. RESULTS: The two groups were well balanced in terms of age, disease histology, tumor stage, tumor location, and performance status (P>0.05). The median follow-up time was 16 months (range, 3–30). The total tumor response rate was 75.0% in group A, which was significantly higher than that in group B (0.0%) (P<0.01). The median progression-free survival time was 4.80 months for patients in group A and 1.35 months for patients in group B (P<0.001). Kaplan–Meier survival analysis showed that the median survival time of group A was 9.4±0.3 months versus 8.4±0.1 months in group B (P=0.013). Tumor-related symptoms of patients were significantly relieved, and the quality of life was markedly improved in group A than in group B. CONCLUSION: CT-guided (125)I brachytherapy improved the survival of patients with locally advanced NSCLC and quality of life after one cycle of first-line chemotherapy compared with best supportive care.